차량주행 모사 조건에서 로드셀을 이용한 인젝터 누적 연료 분사량 측정 - 조성근; Seung Keun Cho; 이충훈; Choong Hoon Lee (한국분무공학회지, 2016)
A gasoline injector rig which can measure cumulative injected fuel mass under a vehicle driving condition was developed. The measurement system consists of an engine control unit (ECU), data acquisition (DAQ) and injected fuel collection system using loadcells. By supplying reconstructed sensor signals which simulate the real vehicle`s sensor signals to the ECU, the ECU drives injectors as if they were driven in the vehicle. The vehicle`s performance was computer simulated by using GT-Suite® software based on both engine part load performance and automatic transmission shift map. Throttle valve position, engine and vehicle speed, air mass flow rate et al. were computer simulated. The used vehicle driving pattern for the simulation was FTP-75 mode. For reconstructing the real vehicle sensor signals which are correspondent to the GT-Suite® simulated vehicle`s performance, the DAQ systems were used. The injected fuel was collected with mess cylinders. The collected fuel mass in the mess cylinder with elapsed time after starting FTP-75 driving mode was measured using loadcells. The developed method shows highly improved performance in fast timing and accuracy of the cumulative injected fuel mass measurement under the vehicle driven condition.